Optimisation of surface sterilization and callus induction of selected Salacca Glabrescens - Ahmad Hilman Ariffin Rusni
The protocol for somatic embryogenesis is genotype dependent thus it is necessary to develop a new protocol for every selected cultivar. Plantlet regeneration can be obtained from two pathways: callus and meristem. These studies emphasized on the preliminary steps (explants selection, sterilization and callus induction) towards somatic embryogenesis of Salacca glabrescens. Screening of explants (young shoot, leaf and flowers) showed that the best was the unfertilized ovaries. Using improved sterilization procedures, the contamination of explants, had been successfully sterilized with 97.5% (Method C) clean culture. Further studies were carried out to improve callus production from S. glabrescens female flowers from selected MARDI cultivars (STI and ST2). Callus induction was obtained using modified Y3 medium, containing the combinations of 2, 4-D, (2, 4 and 6ppm), Picloram (1, 2, and 3ppm) and TDZ (0.1, 0.2 and 0.3ppm). A total of 27 treatments combination were screened, with a treatment; YF14 used as control (4ppm 2, 4-D, 2ppm Picloram and 0.2ppm TDZ). All the treatments were supplied with 7% (w/v) sucrose, 0.1% (w/v) activated charcoal, and 5% (v/v) coconut water. The best result was YF9 gave an average of 58.35% callus, which was higher than an earlier published results of 37% callus (Ainul et. al., 2011). From analysis of variance (ANOVA) there were no significant differences (P> 0.05) when compare treatments with control. Histology studies shows that the callus occurred from the ovule surfaces .